Study of Water Hyacinth of Bangladesh IV: Comparative Study of Pollen Grains and Development of Seed in Both Long and Short Petioled Forms of Eichhornia crassipes (Mart.) Solms-Laubach - Khatun, Rahima; Islam, AS; Majid, FZ (Bangladesh Journal of Scientific and Industrial Research, 2007)
Pollen stainability was found to be more or less similar in long petioled form (LPs) and short petioled form (SPs) of water hyacinth but the size of both oval and round pollen grains was bigger in SPs in comparison to the LPs, the difference being statistically significant. In seed development, significant differences were observed between LPs and SPs at 1 % level only in respect of their average number of capsules and seeds in case of natural pollination. However, in case of artificial self and crosspollinated flowers, significant differences were observed between LPs and SPs at 1 % level in respect of their average number of capsules, seed-bearing capsules and also number of seeds per capsule.Bangladesh J. Sci. Ind. Res. 41(3-4), 189-202, 2006